Solution-processed semiconductors for next-generation photodetectors - Ardalan Armin (Nature Reviews Materials, 2017)
Efficient light detection is central to modern science and technology.Current photodetectors mainly use photodiodes based on crystalline inorganic elementalsemiconductors, such as silicon, or compounds such as III–V semiconductors. Photodetectorsmade of solution-processed semiconductors — which include organic materials, metal-halideperovskites and quantum dots — have recently emerged as candidates for next-generation lightsensing. They combine ease of processing, tailorable optoelectronic properties, facile integrationwith complementary metal–oxide–semiconductors, compatibility with flexible substrates andgood performance. Here, we review the recent advances and the open challenges in the field ofsolution-processed photodetectors, examining the topic from both the materials and the deviceperspective and highlighting the potential of the synergistic combination of materials and deviceengineering. We explore hybrid phototransistorsand their potential to overcome trade-offsin noise, gain and speed, as well as the rapid advances in metal-halide perovskite photodiodesand their recent application in narrowband filterless photodetection.